1992
DOI: 10.1111/j.1469-8137.1992.tb00056.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal response of slash pine (Pinus elliottii var. elliottii Engelm.) photosynthesis to long‐term exposure to ozone and acidic precipitation*

Abstract: summary Four half‐sib families of slash pine (Pinus elliottii var. elliottii) were planted in open‐top chambers and exposed to ozone and simulated acidic precipitation (3: 7 molar ratio of nitric and sulphuric acids). The 4 ozone treatments were (1) charcoal‐filtered air, (2) unfiltered ambient air, (3) twice ambient and (4) three times ambient ozone, with treatments applied 12 h per day, 11 months per year for 28 months. Seedlings were irrigated weekly with one of three rain acidities: pH 33, 4.3 or 5.3 at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

1995
1995
1997
1997

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
(26 reference statements)
1
7
0
Order By: Relevance
“…They found that as tbe leaf area of a plant increases during canopy development, leaf conductance decreases on a unit leaf area basis as canopy transpiration approaches a maximum. We might see an ozone effect on this hydraulic coordination in slash pine because both leaf area and g,, of trees exposed to 2X and 3X ozone tended to be lower than in the trees in the CF and NF treatments (Byres et al 1992a; Figs 3, 4). This suggests that the ozone treatments might be reducing the hydraulic capacity of the roots and stems which, in turn, is affecting the equihbrium level of the co-ordination proposed by Meinzer & Grantz (1991).…”
Section: Discl'ssionmentioning
confidence: 99%
See 4 more Smart Citations
“…They found that as tbe leaf area of a plant increases during canopy development, leaf conductance decreases on a unit leaf area basis as canopy transpiration approaches a maximum. We might see an ozone effect on this hydraulic coordination in slash pine because both leaf area and g,, of trees exposed to 2X and 3X ozone tended to be lower than in the trees in the CF and NF treatments (Byres et al 1992a; Figs 3, 4). This suggests that the ozone treatments might be reducing the hydraulic capacity of the roots and stems which, in turn, is affecting the equihbrium level of the co-ordination proposed by Meinzer & Grantz (1991).…”
Section: Discl'ssionmentioning
confidence: 99%
“…Similar results and conclusions were reported for poplars exposed to ozone (Reich & Lassoie, 1984). By contrast, Chappelka, Chevone & Seiler (1988), using multiple regression analysis on data for young yellow-poplar (Liriodendron tulipifera) seedlings, reported that the slope for the VPD parameter was increased in the ozone treatment. They interpreted this as an increased sensitivity of the stomata to VPD.…”
Section: Discl'ssionmentioning
confidence: 99%
See 3 more Smart Citations